Optimal supply chain design: a comparison of individual factories and industrial clusters allocation - Vanzetti, Nicolás (2016)
The aim of this work is to present a mathematical model for the optimal design and planning of a supply chain, where several plants that produce different products can be installed forming clusters. In order to analyze facilities integration, discounts in installation and production costs are assumed. In addition, the tradeoffs between clusters and individual facility configurations are assessed. This work also focuses on the effect of the production scale in the overall SC, and the costs reduction when plants share resources and services.